Juan de Pastrana y su singular clasificación de la dictio dentro de la gramática del s. XV (Minerva. Revista de Filología Clásica, 2019)
In this paper the author examines the singular classification of the dictio in three classes made by the XVth-century Spanish grammarian Juan de Pastrana in his Compendium grammaticae. Moreover, possible influences for such a classification are looked for in logical and grammatical tradition. Finally, this tripartite division is related to the similar ones carried out by Ramus and Sanctius in the XVIth century.